Radiometric and geoelectric response of karst structures in Mahendra and Chamero Caves, Pokhara Valley, Nepal - Gautam, Pitambar; Pant, Surendra Raj; Ando, Hisao; Wagle, Raghu Nath (Journal of Nepal Geological Society, 2000)
Natural gamma ray intensity and electrical resistivity measurements were made over the karst features (subsurface flow channels, solution cavities, and sinkholes) forming the Mahendra and Chamero Caves in the Pokhara Valley, central Nepal. The layered basin-filling Quaternary elastic sediments comprising gravel, silt, and clay constitute the upper 60-80 m section of the Pokhara Valley. Depending mainly on lithology, they differ widely in electrical resistivity (a few hundred s to several tens of thousands of Ohm m) making them suitable for mapping by resistivity methods. In favourable cases, electrical imaging is useful for assessing the layered structure as well as localised void spaces. Total gamma ray intensity profiles reveal significant anomalies (up to 100 counts per second) over the subsurface openings. The gamma-ray method is sensitive to near-surface cavities and is effective in locating the karstified structures, whereas the electrical images provide quantitative estimates of the depth to such features.